Epidermoid cyst of the ovary: A case report - Özercan, I.H. (My University, 2000)
In the ovary, epidermoid cysts are rare and their origin is controversial. This rare lesion was uniformly an incidental finding in the study of hysterectomy specimens. The patient was a 48-year-old woman. Because of multiple leiomyomas she had a total hysterectomy and bilateral salpingo-oopherectomy operation. A Epidermoid cyst was found incidentally in the right ovary on the microscobic examination.
Keywords: Epidermoid cyst; Ovary